The extractive industries as a primer for economic growth - getting around the resource curse. - Lokanc, Martin (My University, 2008)
ABSTRACT One of the surprising features of modern economic growth is that economies with abundant natural resources have tended to grow less rapidly than natural resource scarce economies. This paper demonstrates that countries with high levels of natural resource exports tend to grow slower than those countries that have fewer natural resource exports. However, when controlling for the quality of institutions, the effect can be reversed. It is has been found that all countries (regardless of the intensity of natural resource exports) perform better under „good‟ institutions than under „poor‟ institutions. Furthermore, the study examines the determinates of good institutions and finds that high levels of social and human capital are pre-requisites for strong institutions and good governance. The data therefore suggests that high stocks of human and social capital are possible cures to the resource curse. The study further concludes that although resource abundance is linked to slower levels of economic growth, countries should not turn a blind eye to their natural resources. They should however not depend on them too much as the benefits of resource based industrialisation and „forced‟ beneficiation are questioned. The study has implications for policy makers as it recommends that a blank page approach be taken when formulating a development strategy. In terms of institutional reform, the study examines various forms of government in Africa against economic success and finds that African countries perform better under democracies. This finding is likely linked to the mode of manifestation of the resource curse. In Africa, the resource curse seems to specifically manifest itself through the political economy (including systems of political patronage, conflict and security) and not through the effects of macro-economic instability (i.e. Dutch disease). Furthermore, a geographical study of institutions, human capital and economic performance suggests that good performance spills over into adjacent countries, thereby creating a case for increased regionalisation in Africa and recommends more bilateral trade and interdependency of African economies to spread good practices.